PTIMIZATION AND CHARACTERIZATION OF USED COOKING OIL FOR BIODIESEL PRODUCTION USING RESPONSE SURFACE METHODOLOGY - Umar, Khadijah Aminu; Adedo, Ahmad Akanbi; Muhammad , Aminu; Sa'eed, Ahmad; Muhammad , Abdulladif; AbdulLateef, AbdulHakeem; Gama, Ibrahim Auwal; Tijani, Husseini (FUDMA JOURNAL OF SCIENCES, 2023)
This study focuses on optimizing and characterizing alkali-catalyzed biodiesel production from used cooking oil. Transesterification using potassium hydroxide (KOH) and methanol, followed by solvent-solvent extraction, yielded biodiesel. Physicochemical analysis of the used cooking oil revealed an acid value of 29 mgNaOH/g, free fatty acid (FFA) value of 14.5, and density of 0.91 g/cm3. The high FFA content suggests the use of a heterogeneous catalyst. Optimization parameters included alcohol-to-oil ratio, catalyst concentration, reaction temperature, and time, employing Response Surface Methodology (RSM) based on Central Composite Design (CCD). Optimal conditions for biodiesel production were determined at a reaction temperature of 60°C, a reaction time of 60 minutes, 0.3g KOH catalyst concentration, and a 3:20 methanol-to-oil ratio, predicting a 100% yield. Physiochemical properties of the produced biodiesel indicated specific gravity and pH values of 0.891 and 7.60, respectively. Biodiesel blends (B100, B80, and B20) exhibited specific gravity and pH values of 0.891, 0.842, and 0.839, and 7.60, 7.81, and 5.5, respectively. Comparative analysis with diesel suggests the biodiesel's suitability for standalone or blended use in diesel engines. Characterization involved physicochemical analysis, Fourier Transform Infrared Spectroscopy (FTIR), and Thin Layer Chromatography (TLC). Overall, the optimized process presented a viable and efficient approach to producing biodiesel from used cooking oil with favourable fuel properties